Evaluation of Red Cell Distribution Width and its Correlation with Left Ventricular Ejection Fraction in Heart Failure Patients - Mayank Nausran; Sameeksha Rathi; Amit Bhadauria (National Board of Examinations Journal of Medical Sciences, 2023)
Introduction: Red cell distribution width (RDW) is a coefficient of variation of the distribution of individual RBC volume, as determined by automated blood cell counting instrument. Numerous studies, conducted elsewhere, have demonstrated increased RDW to be a significant prognostic marker in patients with heart failure, both with reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). So, we designed this cross-sectional study, to study the relationship between RDW and left ventricular ejection fraction (LVEF), the most significant echocardiographic parameter of left ventricular systolic function, in patients of heart failure in our region, at a tertiary care centre of North India. Methods: This study was a cross sectional study conducted on 52 patients of heart failure, who attended medical emergency/outpatient services of Guru Nanak Dev Hospital, Amritsar. RDW was assessed with automated analyzer and LVEF was seen by echocardiography in heart failure patients and their association was studied by Pearson Correlation method. Results: LVEF and RDW-CV revealed a Pearson Correlation coefficient of -0.861 which was statistically highly significant (p <0.001), which stayed highly significant even after adjusting for other potential confounding factors like diabetes mellitus (DM), dyslipidemia and hypertension (HTN) Conclusion: Heart failure patients with low LVEF have elevated RDW levels compared with normal LVEF, thus RDW correlated with severity of left ventricular systolic dysfunction.